2016
DOI: 10.1371/journal.pone.0168170
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lasting WNT-TCF Response Blocking and Epigenetic Modifying Activities of Withanolide F in Human Cancer Cells

Abstract: The WNT-TCF signaling pathway participates in adult tissue homeostasis and repair, and is hyperactive in a number of human diseases including cancers of the colon. Whereas to date there are no antagonists approved for patient use, a potential problem for their sustained use is the blockade of WNT signaling in healthy tissues, thus provoking potentially serious co-lateral damage. Here we have screened a library of plant and microorganism small molecules for novel WNT signaling antagonists and describe withanoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…Ivermectin has been shown to promote the expression of several IFN-related genes, such as IFIT1, IFIT2, IF144, ISG20, IRF9, and OASL [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ivermectin has been shown to promote the expression of several IFN-related genes, such as IFIT1, IFIT2, IF144, ISG20, IRF9, and OASL [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…ACTION ON HOST TARGETS FOR VIRAL REPLICATION Level 4: Action as an antiviral IVM has antiviral properties against other viruses including the RNA viruses such as Zika Virus (ZKV), Dengue virus, yellow fever virus (YFV), and West Nile virus (WNV), Hendra virus (HEV), Newcastle virus, Venezuelan equine encephalitis virus (VEEV), Chikungunya virus (CHIKV), Semliki Forest virus (SFV), and Sindbis virus (SINV), Avian influenza A virus, Porcine Reproductive and Respiratory Syndrome virus (PRRSV), Human immunodeficiency virus type 1 as well as DNA viruses such as Equine herpesvirus type 1 (EHV-1) and Pseudorabies virus (PRV). Heidary, F et al 2020 [ 29 ] Level 5: Action on viral replication and assembly In Vero/hSLAM cells infected with the SARS-CoV-2 virus when “exposed” to 5 µM IVM showed a 5000-fold reduction in viral RNA at 48 h when compared to the control group Caly L et al 2020 [ 30 ] utilizing modeling approach, predicted lung accumulation of Ivermectin over 10 times higher than EC 50 Arshad et al 2020 [ 31 ] best binding interaction between IVM and RNA-dependent RNA polymerase (RdRp) Swargiary et al* 2020 [ 33 ] highly efficient binding of IVM to nsp14 Ma et al 2015 [ 35 ] highly efficient binding of IVM to the viral N phosphoprotein and M protein Eweas et al 2021 [ 23 ] Level 6: Action on post-translational processing of viral polyproteins IVM binds to both proteins, Mpro, and to a lesser extent to PLpro of SARS-CoV-2 Eweas et al 2021 [ 23 ] Level 7: Action on Karyopherin (KPNA/KPNB) receptors IVM inhibits the KPNA/KPNB1- mediated nuclear import of viral proteins Caly L et al 2020 [ 30 ] C. ACTION ON HOST TARGETS FOR INFLAMMATION Level 8: Action on Interferon (INF) levels IVM promotes the expression of several IFN-related genes, such as IFIT1, IFIT2, IF144, ISG20, IRF9, and OASL Seth C 2016 [ 40 ] …”
Section: Introductionmentioning
confidence: 99%
“…42 Ivermectin suppressed the sensitivity of human colon cancer xenografts to TCF inhibition without discernible side effects. 42,43 Ivermectin also inhibits lung cancer development in vivo, which supports the possibility of treating WNT-TCF-dependent diseases, such as intestine cancer, breast cancer, skin cancer, and lung cancer, with a blocker of the WNT-TCF pathway response. 42 Moreover, after observing the anti-clonogenic effect of ivermectin through the analysis of spheroid formation, pretreatment with ivermectin in the examined cell lines eliminated floating spheroids by up to 73%, and this effect was accompanied by the suppression of cyclin D1, which demonstrates that ivermectin limits the formation of cancer stem cells.…”
Section: Ivermectin Modulates Several Pathwaysmentioning
confidence: 68%
“…As anti-neoplastic agent, it has been demonstrated that ivermectin exhibit anti-tumoral activity in different types of cancers, with emphasis on ovarian, colon and lung cancers, glioma, leukaemia and melanoma [ 157 , 158 , 159 , 160 , 161 ]. Different mechanisms can explain this activity, namely the inhibition of multidrug resistance proteins (MDR), modulation of protein kinase B (Akt)/mTOR and Wnt/T-cell factor (Wnt/TCF) signalling pathways, degradation of p21–activated kinase (PAK-1) and downregulation of stemness genes to preferentially target CSCs populations [ 158 , 159 , 161 , 162 , 163 , 164 , 165 , 166 , 167 ].…”
Section: Drug Repurposing For Ovarian Cancer Therapymentioning
confidence: 99%